Organizational silence and barriers to early corruption detection: A qualitative study of local governments in North Sulawesi - Brain Fransisco Supit; Jeane Mantiri (Komisi Pemberantasan Korupsi, 2026)
North Sulawesi's Enforcement and Early Corruption Detection Score Index declined from 80,63 (on a 0-100 scale) in 2024 to 65,94 in 2025, nearly twice the national drop, despite a compliance score of 98,63 out of 100 in public services. This integrity paradox signals a decoupling between administrative performance and accountability. Prior studies have examined political capture, organizational silence, and digital governance failures separately; none has mapped their coupling within a local government context. This study investigates the tripartite interrelationship among silence culture, elite political intervention, and digital accountability instrument degradation as the primary explanation for declining early detection capacity within North Sulawesi’s local government oversight system. A qualitative case study was conducted across the Provincial Government of North Sulawesi and City Governments of Manado, Bitung, and Tomohon. Data was collected through interviews, document analysis, and ATLAS.ti thematic coding, analyzed through Principal-Agent Theory, Institutional Theory, and Organizational Silence Theory. Findings reveal a self-reinforcing cycle: elite political intervention hollows out digital instruments including I-Mut /Siladen and the Whistleblowing System; degradation deepens organizational silence; and entrenched silence shields elite intervention from oversight. Minahasan values of Si Tou Timou Tumou Tou and Mapalus, though co-opted to rationalize silence, carry latent normative resources for reform. This study recommends strengthening APIP independence, mandating fiscal allocation for oversight, consolidating whistleblowing platforms, enforcing merit-based sanctions, and reappropriating local wisdom.